Criptocurrency Menurut Kaidah Sadd Adz-Dzari’ah: MAQASHID SYARIAH - bin Lahuri, Setiawan; Mumtaz, Azzam Fatahillah (MAQASID, 2024)
Abstract: The rapid development of the times requires people to follow every change, especially in financial transactions. From bartering to digital cash, things are always changing as technology evolves. The problems that exist in digital money present cryptocurrency as a solution to be used as a transaction tool. The presence of crypto is an answer as well as a new problem in the financial world, so not all countries recognize it as currency. Differences in recognition from various countries must be based on problems in it. In the case of muamalah, Islam has set the conditions that must be met. This article will discuss cryptocurrencies from the perspective of sadd Adz-Dzari'ah which is expected to provide deeper insight into cryptocurrencies from an Islamic point of view. The method used in this writing is descriptive using library research. The results of this study indicate that currently circulating cryptocurrencies still have various problems. Therefore, from the perspective of sadd Adz-Dzari'ah cryptocurrency cannot be used as a transaction tool. Keywords: Cryptocurrency, Sadd Adz-Dzari’ah